2005
DOI: 10.1002/mrm.20575
|View full text |Cite
|
Sign up to set email alerts
|

Contrast‐enhanced 4D radial coronary artery imaging at 3.0 T within a single breath‐hold

Abstract: Coronary magnetic resonance angiography data are usually acquired during mid-diastole of each heartbeat to minimize cardiac motion related artifacts. The proper trigger delay time, which may vary widely among subjects, must be determined individually for each subject before data acquisition to achieve optimal image quality. These complications could be resolved by acquiring contiguous cardiac phase images through the cardiac cycle. In this study, we used a radial sampling technique to acquire 3D cine coronary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…43 However, in patients with fast heart rates, the end systolic pause may be longer and imaging would best be performed at this time. 50 Although 3D cine coronary angiography has been proposed using radial 3 and Cartesian 5 approaches, the temporal resolution achievable is limited and the rationale behind this approach has largely been to avoid the need for determining a subject-specific trigger time and acquisition window, and to enable averaging over those phases where motion is minimal to improve signal-to-noise ratio. Using a 111-148 ms acquisition window for example, Bi et al 3 found that visualization of the right coronary artery was adequate in just 4 out of 16 view-shared cardiac phases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…43 However, in patients with fast heart rates, the end systolic pause may be longer and imaging would best be performed at this time. 50 Although 3D cine coronary angiography has been proposed using radial 3 and Cartesian 5 approaches, the temporal resolution achievable is limited and the rationale behind this approach has largely been to avoid the need for determining a subject-specific trigger time and acquisition window, and to enable averaging over those phases where motion is minimal to improve signal-to-noise ratio. Using a 111-148 ms acquisition window for example, Bi et al 3 found that visualization of the right coronary artery was adequate in just 4 out of 16 view-shared cardiac phases.…”
Section: Introductionmentioning
confidence: 99%
“…50 Although 3D cine coronary angiography has been proposed using radial 3 and Cartesian 5 approaches, the temporal resolution achievable is limited and the rationale behind this approach has largely been to avoid the need for determining a subject-specific trigger time and acquisition window, and to enable averaging over those phases where motion is minimal to improve signal-to-noise ratio. Using a 111-148 ms acquisition window for example, Bi et al 3 found that visualization of the right coronary artery was adequate in just 4 out of 16 view-shared cardiac phases. To image at multiple time-points throughout the cardiac cycle, including when there is rapid motion, requires a short acquisition window which would lead to a prohibitively long study duration with this technique.…”
Section: Introductionmentioning
confidence: 99%
“…This whole-heart approach is feasible at 3T as it is at 1.5T using either breath holding (43,44) or free breathing navigator gated techniques (45). Although, the whole-heart technique at 3T has been shown to be useful for the assessment of coronary artery anomalies (45), its utilization for CAD evaluation has not yet been proven to be possible as it is shown at 1.5T (38, 39).…”
Section: Coronary Imagingmentioning
confidence: 99%
“…Similarly, black blood vessel wall imaging is feasible at 3T and is improved by using adiabatic IR preparatory pulse (22), however, the resolution limits and its application in CAD patients has not been exploited to date. The advantage of prolonged T1 time has also proven to beneficial for contrast enhanced CMRA at high magnetic field (43,44). Further exploitation of this prolonged T1 time can potentially be used for spin labeled CMRA (8).…”
Section: Coronary Imagingmentioning
confidence: 99%
“…have proposed a segmented 3D radial stack-of-stars acquisition approach that generated four consecutive volumes at each temporal sub-window [12], combining these sub-images to improve image quality. Additionally, several other studies have explored coronary acquisition over multiple temporal phases using k-space segmented strategies [6,13] or high-resolution 3D cine approaches [1417] with radial or spiral sampling patterns. In all of the aforementioned multiphase 3D volumetric imaging approaches, the temporal window resolution is defined as the duration of each equally spaced temporal phase, and is not inherently designed for retrospective processing of any desired temporal subset within the acquisition window.…”
Section: Introductionmentioning
confidence: 99%